1994
DOI: 10.1021/bi00209a017
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of forskolin interactions with type I, II, V, and VI adenylyl cyclases by Gs.alpha.

Abstract: Several forms of adenylyl cyclase (types I, II, V, and VI) have been expressed using the recombinant baculovirus expression system in Sf9 cells. The activation of type I adenylyl cyclase by forskolin and Gs alpha was not greater than additive. In contrast, there was synergistic activation of type II, V, and VI adenylyl cyclases by Gs alpha and forskolin. Gs alpha potentiated the effect of forskolin on type II adenylyl cyclase to the greatest extent. Type I and II adenylyl cyclases were photolabeled specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(81 citation statements)
references
References 31 publications
(48 reference statements)
10
70
0
Order By: Relevance
“…2, all three forms of AC were stimulated by G s␣ and forskolin. As described by McHugh-Sutkowski et al (27) for the fulllength ACV, when G s␣ and forskolin were added together, the activity of the full-length enzyme in Sf9 cells was only modestly increased over the sum of the stimulation observed with forskolin and G s␣ alone (Fig. 2C).…”
Section: Resultssupporting
confidence: 74%
“…2, all three forms of AC were stimulated by G s␣ and forskolin. As described by McHugh-Sutkowski et al (27) for the fulllength ACV, when G s␣ and forskolin were added together, the activity of the full-length enzyme in Sf9 cells was only modestly increased over the sum of the stimulation observed with forskolin and G s␣ alone (Fig. 2C).…”
Section: Resultssupporting
confidence: 74%
“…First, several ACs are expressed in the cells assayed here and they have different sensitivities to forskolin. If AC7 is less sensitive to forskolin than other ACs as has been reported for AC2 (39), any synergism may get lost in the large signal from other ACs in the cells. Second, even though an AC can be activated by forskolin, the activation state of the protein appears to have a different conformation than when it is activated by G s (40 -42).…”
Section: Discussionmentioning
confidence: 87%
“…7) Therefore, the increased level of free G s a subunits due to expression of G s protein-coupled receptors with constitutive activity would enhance the responses to forskolin. Alewijnse et al 8) demonstrated that constitutive activity of G s protein-coupled receptors, such as histamine H 2 receptor and thyrotropin receptor, contribute to the enhancement of both basal and forskolin-induced cAMP production in CHO cells.…”
Section: Discussionmentioning
confidence: 99%